2018
DOI: 10.1038/s41393-018-0173-0
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of BDNF-TrkB signaling inhibits the promotion effect of neurological function recovery after treadmill training in rats with spinal cord injury

Abstract: The BDNF-TrkB signaling is a critical pathway in exercise training that promotes the recovery of neurological function in rats with incomplete SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 34 publications
1
40
0
Order By: Relevance
“…PSD-95 is constituent of the postsynaptic membrane that plays a key role in the plasticity and structure of the excitatory chemical synapse (Wu et al, 2017 ), and multiple studies have associated physical exercise with its induction (Jung and Kim, 2017 ; Pan et al, 2017 ). A series of studies have shed light on the relationship between these factors by demonstrating that BDNF/NGF participate in promoting neuroplasticity for motor rehabilitation after focal cerebral infarction (Matsuda et al, 2011 ; Mizutani et al, 2011 ; Mang et al, 2013 ); BDNF was reported to be induced by exercise, and may regulate the expression of synaptic proteins including GAP-43 (Liu W. et al, 2018 ), SYN (Ferreira et al, 2011 ), PSD-95 (Li X. et al, 2019 ) and Tau (Kerling et al, 2017 ). This research indicates that synaptic plasticity after stroke is determined, at least in part, by the induction and upregulation of axonal or synaptic proteins that, in our study, were found to be increased in both exercise cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…PSD-95 is constituent of the postsynaptic membrane that plays a key role in the plasticity and structure of the excitatory chemical synapse (Wu et al, 2017 ), and multiple studies have associated physical exercise with its induction (Jung and Kim, 2017 ; Pan et al, 2017 ). A series of studies have shed light on the relationship between these factors by demonstrating that BDNF/NGF participate in promoting neuroplasticity for motor rehabilitation after focal cerebral infarction (Matsuda et al, 2011 ; Mizutani et al, 2011 ; Mang et al, 2013 ); BDNF was reported to be induced by exercise, and may regulate the expression of synaptic proteins including GAP-43 (Liu W. et al, 2018 ), SYN (Ferreira et al, 2011 ), PSD-95 (Li X. et al, 2019 ) and Tau (Kerling et al, 2017 ). This research indicates that synaptic plasticity after stroke is determined, at least in part, by the induction and upregulation of axonal or synaptic proteins that, in our study, were found to be increased in both exercise cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…One week before SCI, the L3-4 intrathecal catheter operation was conducted to observe whether this operation injured the spinal cord or nerve. 28 Briefly, all rats were anesthetized by intraperitoneal injection of 10% chloral hydrate (0.3 ml/100g). The interspace between the L3-4 spinous process was located and exposed, and the dura mater and subarachnoid cavity were broken through with a 19G puncture needle.…”
Section: Intrathecal Catheter and Scimentioning
confidence: 99%
“…As changes in GAP-43 and SYN expression levels in the injured SC have signi cant effects on improving motor function, an increase in these factors in the cMSC group may have contributed to improved motor function. In previous studies, BDNF enhanced GAP-43 and SYN expression in neurons through the Trk receptor and subsequent ERK/CREB signaling [50,51]. The promotion of GAP-43 and SYN expression may be mediated by endogenous BDNF of SC tissue that is increased by cMSC transplantation.…”
Section: Discussionmentioning
confidence: 77%